BLOOD UREA NITROGEN AND CREATININE LEVELS IN BROILER CHICKENS FED WITH ORGANIC ACIDS - Faradina, Elfani Sarah; Utama, Iwan Harjono; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2022)
Organic acids are a mix of various compounds of organic carboxylic acids and are used as an acidifier in chicken feed. Organic acids could increase the digestibility and absorption of protein in broiler chicken, because organic acids can inhibit pathogenic bacterial growth in the gastrointestinal tract. The increase of protein absorption can affect the level of blood urea nitrogen and creatinine in broiler chicken’s blood, which is considered parameters for kidney function. The objective of this study is to determine the Blood urea nitrogen (BUN) and creatinine levels in 24 female broiler chickens in the course of 35 days of organic acids treatment. This study used an experimental method with completely randomized design (RAL) consisting of 4 treatments, the control group were only given finished feed (P0), then administered with Orgacids ® as much as 0.1% (P1), 0.2% (P2), and  0.3% (P3). The results showed that the administration of organic acid had no significant effect (P>0.05) on the BUN levels in the P1, P2, and P3 groups against the P0 group. And the administration of organic acids also had no significant effect (P>0.05) on creatinine levels in the P1, P2, and P3 groups against the P0 group. It was concluded that the administration of organic acids in the feed does not affect the levels of BUN and blood creatinine in broilers significantly.